Stochastic Blockchain for IoT Data Integrity - Chen, Yu-Jia; Wang, Li-Chun; Wang, Shu (IEEE transactions on network science and engineering, 2020)
This paper proposes a blockchain-based data checking scheme to protect data integrity in Internet of Things (IoT). Traditional data integrity schemes such as symmetric key approaches and public key infrastructure (PKI) suffer from the single-point of failure and network congestion due to the centralized architecture. Motivated by the distributed data authentication in blockchain, we propose to adopt blockchain to ensure the data integrity in IoT networks. However, the existing blockchain scheme cannot be directly applied to IoT nodes with limited computing and network resources. Hence, we develop a stochastic blockchain scheme to limit the number of cooperative nodes and distribute the load to IoT edge nodes. In our scheme, the IoT data are broadcast by randomly selected cooperative nodes, thereby introducing uncertainty to the attacker and improving the system security level. Finally, we propose a lightweight mining process to make only the IoT edge nodes compete for block generation and share the block with other nodes. If our scheme is used in the case of having 9,000 legitimate nodes and 1,000 compromised nodes, only three cooperative nodes can achieve the probability of successful defense over 99 percent.